5-methyltetrahydrofolate rapidly improves endothelial function and decreases superoxide production in human vessels: effects on vascular tetrahydrobiopterin availability and endothelial nitric oxide synthase coupling. - Antoniades, C; Shirodaria, C; Warrick, N; Cai, S; de Bono, J; Lee, J; Leeson, P; Neubauer, S; Ratnatunga, C; Pillai, R; Refsum, H; Channon, K (2006)
BACKGROUND: The circulating form of folic acid, 5-methyltetrahydrofolate (5-MTHF), may have beneficial effects on endothelial function; however, its mechanisms of action remain uncertain. Decreased nitric oxide (NO) bioavailability and increased vascular superoxide production in vascular disease states are due in part to endothelial NO synthase (eNOS) uncoupling related to deficiency of the eNOS cofactor tetrahydrobiopterin (BH4), but whether this mechanism is important in human atherosclerosis and represents a rational therapeutic target remains unclear. We hypothesized that 5-MTHF would improve endothelial function by decreasing superoxide and peroxynitrite production and by improving eNOS coupling, mediated by BH4 availability. METHODS AND RESULTS: Vascular superoxide/peroxynitrite production and vasomotor responses to acetylcholine and bradykinin were determined in saphenous veins and internal mammary arteries from 117 patients undergoing CABG. The effects of 5-MTHF were examined ex vivo (n = 61) by incubating vessels with 5-MTHF (1 to 100 micromol/L) and in vivo by intravenous infusion of 5-MTHF or placebo before vessel harvest (n = 56). 5-MTHF improved NO-mediated endothelium-dependent vasomotor responses and reduced vascular superoxide, both ex vivo and in vivo. These changes were not explained by direct superoxide scavenging by 5-MTHF in vitro or by changes in plasma total homocysteine in vivo. Rather, 5-MTHF was a strong peroxynitrite scavenger and increased vascular BH4 and the BH4/total biopterin ratio. Furthermore, 5-MTHF reversed eNOS uncoupling, as assessed by NG-nitro-l-arginine methyl ester-inhibitable superoxide production, increased the eNOS dimer:monomer ratio, and enhanced eNOS activity. CONCLUSIONS: 5-MTHF has beneficial effects on endothelial function and vascular superoxide production in human atherosclerosis, by preventing peroxynitrite-mediated BH4 oxidation and improving eNOS coupling.